Kontrol Keimigrasian terhadap Kunjungan Orang Asing di Provinsi Aceh - Safrida Safrida (Asia-Pacific Journal of Public Policy, 2019)
The government, through the Directorate General of Immigration, an Indonesian government agency under the Ministry of Law and Human Rights, has carried out one of its duties and functions, namely the supervision and control of foreigners residing in Indonesian territory, based on Law Number 6, 2011 concerning Immigration. The supervision or control is carried out to enforce the law, especially the immigration law. The class II Lhokseumawe Immigration Office in the Aceh province, which is the technical implementation unit for immigration in the region, has carried out its duties and functions of monitoring and controlling foreigners in its working area since the release of regulation No. 6, 2011. The results of this study reported that the implementation of supervision of foreigners at the Lhokseumawe Immigration Office has been carried out properly based on the regulation concerning Immigration and Regulation of the Minister of Law and Human Rights. But some constraints are still encountered, particularly lack of supervisory staff number, the width of the working area, and the limited budget. The author's suggestion should be that the implementation of supervision and control of foreigners at this working area should be carried out as often as possible and at the same time, the stakeholder (government) should resolve the obstacles met by staffs so that the immigration law enforcement can be achieved and improved.